1999
DOI: 10.1074/jbc.274.35.25159
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Cyclodextrin-specific, Unusual Porin from Klebsiella oxytoca

Abstract: The function of CymA, 1 of the 10 gene products involved in cyclodextrin uptake and metabolism by Klebsiella oxytoca, was characterized. CymA is essential for growth on cyclodextrins, but it can also complement the deficiency of a lamB (maltoporin) mutant of Escherichia coli for growth on linear maltodextrins, indicating that both cyclic and linear oligosaccharides are accepted as substrates. CymA was overproduced in E. coli and purified to apparent homogeneity. CymA is a component of the outer membrane, is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 45 publications
2
41
0
2
Order By: Relevance
“…Our study revealed that chitohexaose is the most potent substrate of the VhChiP channel, as it blocked the ion flow even at nanomolar concentrations, and the monomeric subunit was already saturated below 1 M. In Table 2, we summarize the rate constants: the on-rate (k on ) is by far the highest for chitohexaose, whereas the off-rate (k off ) is the lowest. Consequently, the resultant binding constant (K) of 5.0 ϫ 10 6 M Ϫ1 is 1-5 orders stronger than the reported values for other analogs (25,31,(35)(36)(37)(38)(39)(40). According to the kinetic data in Table 2, VhChiP is the most active sugar-specific channel reported to date.…”
Section: Discussionmentioning
confidence: 75%
“…Our study revealed that chitohexaose is the most potent substrate of the VhChiP channel, as it blocked the ion flow even at nanomolar concentrations, and the monomeric subunit was already saturated below 1 M. In Table 2, we summarize the rate constants: the on-rate (k on ) is by far the highest for chitohexaose, whereas the off-rate (k off ) is the lowest. Consequently, the resultant binding constant (K) of 5.0 ϫ 10 6 M Ϫ1 is 1-5 orders stronger than the reported values for other analogs (25,31,(35)(36)(37)(38)(39)(40). According to the kinetic data in Table 2, VhChiP is the most active sugar-specific channel reported to date.…”
Section: Discussionmentioning
confidence: 75%
“…In the absence of the cymA gene, growth on CDs is lost (4). In addition, CymA confers to an E. coli ΔlamB strain the ability to use maltopentaose and maltohexaose for growth (5). These data indicate that CymA functions as an efficient OM uptake channel for α-and β-CD as well as for linear maltooligosaccharides.…”
mentioning
confidence: 72%
“…Several bacterial proteins bind or transport CDs (CymE, CymA, and CycB) (20,22,95,96). Their affinities for CDs range from 30 M to 3 mM depending on the protein and the CD.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, CDs have been referred to as "molecular adapters" (21). In contrast, CDs appear to fully block the ionic conductance of CymA pores (20,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation